A new AHP – based reactive power valuation method - Kimbin, Daniel (2013)
In Malaysia, the electricity tariff is based on the active energy consumed and does not include any reactive (energy) power required. In order to recover the extra cost incurred in supplying the reactive power required by the consumers, the utility imposes a surcharge on a consumers whose power factor averaged over a month is below the value of 0.85pf. However, the surcharge is imposed on medium to large commercial and industrial consumers only. This paper proposes a new method for valuation of Reactive Power in power system. This method uses two important factors to determine the most important Reactive Power source power system. These two factors are: Voltage Sensitivities and Voltage Adequacy and Stability (PV Curve). In this paper AHP method has been used to classify the Reactive power sources according to their importance in power system. The effectiveness of the proposed method is verified under IEEE 9-bus system.